New findings in Colombia of Panstrongylus geniculatus (Latreille, 1811) and Triatoma dispar Lent, 1950 (Hemiptera: Reduviidae (Colombia Medica, 1988)
The geographical distribution of Panstrongylus geniculatus and Triatoma dispar is extended for Colombia in 6 localities of the Pacific coast (departments of Cauca, Chocó, and Valle del Cauca) and one of the Department of Huila. The importance of these insects in the epidemiology of trypanosomiasis is discussed.